The gap and two-level differentiation in kindergarten education funding groups in China - Chen, Jiantao; Wang, Xiao; Luo, Xiang (Frontiers in Psychology, 2022)
This paper studies the gap in kindergarten education funds between different groups in China from 2012 to 2018 through the Gini coefficient and decomposition technology. The results show that (1) the Gini coefficient of the inter-provincial kindergarten education funds in China has increased during the observation period, (2) although the value of the Gini coefficient between urban and rural areas is lower than that between provinces, it is growing rapidly, (3) from the perspective of the source of education funds, the main reason for the gap in kindergarten education funds at this stage is the uneven distribution of national financial education funds and undertaking revenue, (4) the internal uneven distribution between urban and rural areas and that between regions also contribute a lot to the overall gap, and (5) there is no obvious polarization of kindergarten education funds. Based on the analysis results, the following suggestions are put forward: (1) the Chinese government should increase the investment in education funds and gradually reduce the proportion of school fees income in undertaking revenue, (2) the financial resources should be tilted to kindergartens in regions with relatively slow economic development, and (3) the financial funds should be properly distributed in public and private kindergartens. The main contributions of this paper are as follows: first, it expands the scope of research on the gap in education funding, and analyzes the gap between groups with different sources of education funding; secondly, it enriches the research methods of education funding gap by using a variety of Gini coefficient and decomposition techniques, and calculates the polarization indicators to study the education funding gap in kindergartens; third, it provides some inspiration for Chinese governments and financial institutions at all levels to improve the distribution system of kindergarten education funds and promote the fairness of financial resources at the kindergarten stage.